Highly conductive carbon-coated current collector with reduced surface defects and preparation method and application thereof
Patent Information
- Application Number
- CN202611286482.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0039](1)本申请采用可碳化聚电解质润湿剂作为双功能添加剂,在浆料涂布阶段通过聚乙二醇链段降低表面张力,显著改善水性碳浆料在集流体基材表面的铺展性,有效消除白点、缩孔等膜面缺陷,提升产品良率;在后续热处理阶段,润湿剂分子中的苯磺酸盐基团与聚乙烯亚胺主链发生原位碳化,在相邻导电碳颗粒之间形成导电碳桥,从本质上优化导电网络结构,降低涂层接触电阻,实现一剂双效的技术效果,突破了传统添加剂功能单一的局限。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery manufacturing technology, and relates to a carbon-coated current collector, and more particularly to a highly conductive carbon-coated current collector that reduces film surface defects, its preparation method and application. Background Technology
[0002] With the rapid development of new energy vehicles and portable electronic devices, high-energy-density and high-power-density lithium-ion batteries have become a research hotspot in the energy storage field. As a crucial component of lithium-ion batteries, the current collector is responsible for collecting the current generated by the electrode active materials and outputting it externally. Its conductivity and interfacial bonding state directly affect the battery's internal resistance, rate performance, and cycle life.
[0003] To reduce the contact resistance between the current collector and the active material layer, the industry commonly employs a technique of coating the surface of aluminum or copper foil with a conductive carbon coating, known as carbon-coated current collectors. The carbon coating increases the contact area between the current collector and the active material, reduces interfacial impedance, and improves the conductivity and uniformity of the electrode. However, in the actual production process of carbon-coated current collectors, the coating quality of the water-based carbon slurry on the metal foil surface remains a key factor restricting product yield and performance.
[0004] Due to the high surface tension of aqueous systems and the differences in surface energy of metal foils, aqueous carbon slurries often suffer from insufficient wettability during coating, leading to defects such as white spots, gray spots, pinholes, and incomplete coating on the coated film. These defects not only directly reduce the product's appearance yield but also trigger a series of electrochemical and safety hazards: First, the current collector is locally exposed at the defect location, which easily becomes a current concentration point and a preferential growth site for lithium dendrites during charging and discharging, increasing the risk of internal short circuits; second, film defects disrupt the continuity of the conductive coating network, resulting in uneven distribution of in-plane resistance and impairing the battery's rate performance and batch consistency; third, the defect edges easily become stress concentration areas, accelerating coating peeling during cycling and affecting the battery's long-term cycle stability.
[0005] To address the aforementioned wetting issues, existing technologies typically employ the addition of small-molecule wetting agents, such as isopropanol, ethanol-based alcohol additives, or low-molecular-weight surfactants. While these small-molecule wetting agents can reduce the surface tension of the slurry and improve coating spreadability to some extent, their function is limited to the slurry preparation and coating stages. During the subsequent drying process, most of them evaporate with the solvent or migrate to the coating surface, failing to substantially contribute to the conductivity and interfacial adhesion of the final coating. Furthermore, some residual small molecules can easily disrupt the cross-linking network of the binder, affecting the mechanical properties and adhesion of the coating.
[0006] Furthermore, to further improve the conductivity of the carbon coating, existing technologies typically increase the amount of conductive carbon material or introduce expensive nano-conductive materials. However, simply increasing the amount of conductive agent has a significant marginal effect; once the conductive agent content reaches a certain threshold, the improvement in conductivity tends to plateau, and excessive conductive agent inevitably crowds out the proportion of binder, leading to decreased coating flexibility, increased brittleness, and reduced adhesion to the substrate. While introducing special nano-conductive materials such as carbon nanotubes and graphene can effectively improve conductivity, these materials are expensive and difficult to disperse in aqueous systems, requiring the addition of dispersants or complex surface modifications, further increasing process complexity and production costs. Moreover, uneven dispersion can introduce new film defects.
[0007] In summary, in existing carbon coating current collector technologies, improving slurry wetting and enhancing coating conductivity are two independent technical directions, each relying on different types of additives. There is a lack of synergy between the two, and they even restrict each other: wetting agents only improve the spreadability of the coating process without contributing to the final conductivity, while conductivity enhancement depends on increasing the amount of conductive agent or introducing expensive nanomaterials, making it difficult to improve conductivity while ensuring film quality.
[0008] Therefore, it is evident that how to provide a novel carbon-coated current collector that simultaneously addresses the issues of film surface defects and conductive network optimization, thereby improving the production yield and electrochemical performance of lithium-ion batteries, has become an urgent problem for those skilled in the art. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the purpose of this application is to provide a highly conductive carbon-coated current collector that reduces film surface defects, its preparation method, and its application. By using a single additive, it simultaneously improves slurry wetting and enhances coating conductivity, thereby reducing film surface defects and improving conductivity.
[0010] To achieve this objective, the present application adopts the following technical solution:
[0011] In a first aspect, this application provides a highly conductive carbonized current collector that reduces film surface defects, comprising a current collector substrate and a conductive coating formed on at least one side of the current collector substrate, wherein the raw materials for preparing the conductive coating include at least a carbonizable polyelectrolyte wetting agent.
[0012] The carbonizable polyelectrolyte wetting agent is a polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer.
[0013] This application introduces a carbonizable polyelectrolyte wetting agent into the conductive coating of a carbon-coated current collector. Different functional segments in its molecular structure play a role in different stages of the process: in the coating stage, polyethylene glycol segments provide wetting and spreading functions, reducing film defects; in the heat treatment stage, benzene sulfonate groups and polyethyleneimine main chain are carbonized in situ to form conductive carbon bridges, enhancing the conductive network of the coating. Thus, a single additive can simultaneously improve slurry wetting and enhance coating conductivity, achieving a double leap in processing yield and electrochemical performance of the carbon-coated current collector.
[0014] And / or, the carbonizable polyelectrolyte wetting agent is added to the slurry in the form of an aqueous solution, wherein the solid content of the aqueous solution is 5wt% to 10wt%, and the amount of the aqueous solution added is 5% to 20% of the total mass of the slurry.
[0015] And / or, the raw materials for preparing the conductive coating may also include conductive agents, binders, and pH adjusters.
[0016] And / or, the conductive agent includes carbon black and / or graphite.
[0017] And / or, based on the dry weight of the conductive coating, the amount of the conductive agent added is 50wt%~60wt%.
[0018] And / or, the adhesive comprises at least one of polyacrylic acid, waterborne acrylate copolymer, carboxymethyl cellulose or styrene-butadiene rubber, with a viscosity of 800 mPa·s to 3500 mPa·s.
[0019] And / or, based on the dry weight of the conductive coating, the amount of adhesive added is 40wt%~50wt%.
[0020] And / or, the pH adjuster includes sodium hydroxide and / or sodium carbonate.
[0021] And / or, the current collector substrate includes any one of aluminum foil, copper foil, nickel foil, or titanium foil.
[0022] And / or, the thickness of the conductive coating on one side is 0.5μm to 3μm.
[0023] Secondly, this application provides a method for preparing a highly conductive carbon-coated current collector as described in the first aspect, comprising at least: adding a carbonizable polyelectrolyte wetting agent to a base slurry, stirring and homogenizing the slurry, coating the resulting slurry onto at least one side surface of the current collector substrate, and drying and heat-treating the slurry to obtain the highly conductive carbon-coated current collector.
[0024] The preparation method provided in this application adopts a stepwise dispersion process. First, a stable base slurry is prepared, and then a bifunctional wetting agent is introduced to avoid interference of the wetting agent with the dispersion process of other materials. The subsequent heat treatment step promotes the in-situ carbonization of the aromatic structure in the wetting agent with the polymer backbone, forming carbon bridges between conductive particles, which fundamentally optimizes the topology and electron transport efficiency of the conductive network.
[0025] And / or, the preparation method of the base slurry includes: first mixing the binder and deionized water, then adding the conductive agent step by step, adjusting the pH value to obtain the base slurry.
[0026] And / or, the conductive agent is added in two steps, and after each step, it is dispersed at a speed of 2000rpm~2600rpm, and the dispersion time of the first step is 25min~35min, and the dispersion time of the second step is 55min~65min.
[0027] And / or, the target pH value of the base slurry is 5 to 7.
[0028] And / or, the carbonizable polyelectrolyte wetting agent is added in the form of an aqueous solution, comprising: first pre-dispersing the carbonizable polyelectrolyte wetting agent in deionized water to form a wetting agent solution, and then adding the resulting wetting agent solution to the base slurry.
[0029] And / or, the pre-dispersion rotation speed is 1200rpm~1400rpm, and the time is 25min~35min.
[0030] And / or, the stirring speed is 10 rpm to 15 rpm, and the stirring time is 30 min to 45 min.
[0031] And / or, the homogenization process is carried out at a pressure of 250 bar to 350 bar, and the number of homogenization cycles is 1 to 3.
[0032] And / or, the drying temperature is 100℃~140℃.
[0033] And / or, the heat treatment temperature is 180℃~250℃, and the time is 8h~16h.
[0034] Thirdly, this application provides a battery electrode sheet containing at least the highly conductive carbon-coated current collector that reduces film surface defects as described in the first aspect.
[0035] And / or, the penetration resistance of the highly conductive carbon-coated current collector is ≤10 mΩ·cm 2 .
[0036] And / or, the number of defects on the film surface of the highly conductive carbon-coated current collector is ≤20 per m. 2 .
[0037] Fourthly, this application provides a battery device comprising at least a highly conductive carbon-coated current collector for reducing film defects as described in the first aspect, or a battery electrode as described in the third aspect.
[0038] Compared with the prior art, this application has the following advantages:
[0039] (1) This application uses a carbonizable polyelectrolyte wetting agent as a dual-function additive. In the slurry coating stage, the surface tension is reduced by polyethylene glycol segments, which significantly improves the spreadability of water-based carbon slurry on the surface of the current collector substrate, effectively eliminates film defects such as white spots and pinholes, and improves product yield. In the subsequent heat treatment stage, the benzene sulfonate groups in the wetting agent molecule undergo in-situ carbonization with the polyethyleneimine backbone, forming a conductive carbon bridge between adjacent conductive carbon particles. This fundamentally optimizes the conductive network structure, reduces the coating contact resistance, and achieves the technical effect of dual-function additives, breaking through the limitation of single function of traditional additives.
[0040] (2) This application promotes the uniform dispersion of conductive agent and breaks carbon black agglomerates by generating electrostatic adsorption and anchoring effect between the cationic amine groups on the main chain of polyethyleneimine and the negatively charged carbon black surface during the slurry stage, thus laying the foundation for building a high-quality conductive network. The carbon bridge formed by in-situ carbonization firmly bridges adjacent conductive particles and fills the insulating gaps between particles. Its conductivity enhancement effect is far superior to that of simply physical blending more conductive agents, and it does not damage the mechanical properties and adhesion of the coating.
[0041] (3) The preparation method provided in this application has good process compatibility. The bifunctional wetting agent is a water-soluble material that can be directly integrated into the existing preparation process of water-based carbon coating slurry without adding complex equipment or changing the existing process line, which is convenient for industrial promotion and application. Detailed Implementation
[0042] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0043] One embodiment of this application provides a highly conductive carbonized current collector that reduces film surface defects, comprising a current collector substrate and a conductive coating formed on at least one side surface of the current collector substrate, wherein the raw materials for preparing the conductive coating include at least a carbonizable polyelectrolyte wetting agent.
[0044] The carbonizable polyelectrolyte wetting agent is a polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer.
[0045] The carbonizable polyelectrolyte wetting agent used in this application is a molecularly integrated bifunctional material. Its structural design and mechanism of action are as follows: Polyethyleneimine, as the main chain, provides abundant cationic amine groups, which can generate strong electrostatic adsorption and anchoring effects with the negatively charged carbon black particle surface, playing the role of a polymeric dispersant, promoting the stable and uniform dispersion of conductive particles in the slurry, breaking the original agglomerates, and constructing a better initial conductive network; Polyethylene glycol segments, as strongly hydrophilic side chains, effectively reduce the surface tension of the slurry, enhance the spreading and penetration ability of the slurry on high surface energy metal foils, eliminate bubbles and "coffee ring" effects caused by incomplete wetting, and significantly reduce film defects such as white spots and pinholes; The benzene ring structure in the benzenesulfonate group undergoes cross-linking and carbonization during high-temperature heat treatment, forming a robust amorphous carbon skeleton. At the same time, the polyethyleneimine segments adsorbed on the surface of carbon black particles are also carbonized simultaneously, firmly bridging adjacent carbon black particles, filling the insulating gaps between particles, and greatly reducing the contact resistance between particles.
[0046] In short, this application achieves two functions—wetting and spreading as well as in-situ conductivity enhancement—by using a single additive at different stages of the process. This overcomes the limitation of the separation of functions between wetting agent and conductivity enhancer in traditional carbon coating current collectors, and simultaneously improves film quality and optimizes conductivity.
[0047] In some embodiments, the carbonizable polyelectrolyte wetting agent is added to the slurry in the form of an aqueous solution, and the solid content of the aqueous solution is 5wt% to 10wt%, for example, it can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, or 10wt%. The amount of the aqueous solution added is 5% to 20% of the total mass of the slurry, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, or 20%, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0048] This application adds a carbonizable polyelectrolyte wetting agent in the form of an aqueous solution, that is, it pre-disperses the wetting agent solution separately before adding it to the slurry. This is to avoid the swelling and clumping problem that occurs when the wetting agent powder is added directly, and to ensure that the wetting agent is quickly and evenly distributed in the slurry.
[0049] In addition, this application limits the amount of wetting agent added to the above range. If the amount added is too low, the wetting effect will be insufficient, and the defects on the film surface will not be effectively eliminated. Moreover, the number of conductive carbon bridges formed by in-situ carbonization is limited, and the conductivity enhancement effect is not obvious. If the amount added is too high, too many non-conductive components will be introduced, which will lead to an increase in the internal resistance of the coating. Furthermore, excessive polymers can easily affect the curing of the adhesive and the adhesion of the coating.
[0050] In some embodiments, the raw materials for preparing the conductive coating also include conductive agents, binders, and pH adjusters.
[0051] In some embodiments, the conductive agent comprises carbon black and / or graphite, preferably a combination of carbon black and graphite, and more preferably a mass ratio of carbon black to graphite of 1:(1~3), for example, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8 or 1:3, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0052] This application uses a carbon black and graphite composite as a conductive agent. The carbon black particles are small in size and have a large specific surface area, which can build a rich point contact conductive network. The graphite sheet structure provides a surface contact conductive path. The two work together to achieve comprehensive conductivity in both the longitudinal and transverse directions.
[0053] In some embodiments, the amount of conductive agent added is 50wt% to 60wt%, calculated based on the dry weight of the conductive coating. For example, it can be 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, or 60wt%, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0054] In some embodiments, the adhesive comprises at least one of polyacrylic acid, waterborne acrylate copolymer, carboxymethyl cellulose, or styrene-butadiene rubber, preferably polyacrylic acid, with a viscosity of 800 mPa·s to 3500 mPa·s, for example, 800 mPa·s, 900 mPa·s, 1000 mPa·s, 1200 mPa·s, 1500 mPa·s, 1800 mPa·s, 2000 mPa·s, 2200 mPa·s, 2500 mPa·s, 2800 mPa·s, 3000 mPa·s, or 3500 mPa·s, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0055] This application limits the viscosity of the adhesive to the above-mentioned range, which ensures that the adhesive has suitable rheological properties in the slurry, effectively bonding conductive particles to the substrate, without causing dispersion difficulties or uneven coating due to excessive viscosity.
[0056] In some embodiments, the amount of adhesive added is 40wt% to 50wt%, calculated based on the dry weight of the conductive coating. For example, it can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0057] In some embodiments, the pH adjuster includes sodium hydroxide and / or sodium carbonate, preferably sodium hydroxide.
[0058] In some embodiments, the current collector substrate includes any one of aluminum foil, copper foil, nickel foil, or titanium foil.
[0059] For the positive electrode current collector of a lithium-ion battery, aluminum foil is preferred; for the negative electrode current collector, copper foil is preferred.
[0060] In some embodiments, the thickness of the conductive coating on one side is 0.5μm to 3μm, for example, it can be 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm or 3μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0061] One embodiment of this application also provides a method for preparing the highly conductive carbon-coated current collector described in any of the above embodiments, which includes at least: adding a carbonizable polyelectrolyte wetting agent to a base slurry, stirring and homogenizing the slurry, coating the resulting slurry onto at least one side surface of the current collector substrate, and drying and heat-treating the slurry to obtain the highly conductive carbon-coated current collector.
[0062] The preparation method provided in this application adopts a stepwise dispersion process. First, a stable base slurry is prepared, and then a bifunctional wetting agent is introduced to avoid interference of the wetting agent with the dispersion process of other materials. The subsequent heat treatment step promotes the in-situ carbonization of the aromatic structure in the wetting agent with the polymer backbone, forming carbon bridges between conductive particles, which fundamentally optimizes the topology and electron transport efficiency of the conductive network.
[0063] In some embodiments, the preparation method of the base slurry includes: first mixing the binder and deionized water, then adding the conductive agent step by step, adjusting the pH value to obtain the base slurry.
[0064] In some embodiments, the conductive agent is added in two steps, and after each step, it is dispersed at a speed of 2000 rpm to 2600 rpm, for example, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm, or 2600 rpm. The dispersion time of the first step is 25 min to 35 min, for example, 25 min, 26 min, 28 min, 30 min, 32 min, 34 min, or 35 min. The dispersion time of the second step is 55 min to 65 min, for example, 55 min, 56 min, 58 min, 60 min, 62 min, 64 min, or 65 min. However, it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0065] This application employs a stepwise addition of conductive agent combined with high-speed dispersion, which helps to gradually break up the conductive agent agglomerates, achieve uniform dispersion of conductive particles, and avoid uneven dispersion or excessively high slurry viscosity caused by adding the agent all at once.
[0066] In some embodiments, the target pH value of the base slurry is 5 to 7, for example, it can be 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8 or 7, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0067] This application controls the pH value of the base slurry within a weakly acidic range to ensure that the degree of protonation of the amine matrix on the polyethyleneimine backbone is moderate, thus ensuring sufficient cationic charge to exert electrostatic dispersion while avoiding excessive protonation that would cause the polymer chain to stretch excessively and affect the stability of the slurry.
[0068] For example, the pH value of the base slurry can be adjusted using a sodium hydroxide solution with a concentration of 0.5 mol / L to 2 mol / L.
[0069] In some embodiments, the carbonizable polyelectrolyte wetting agent is added in the form of an aqueous solution, including: first pre-dispersing the carbonizable polyelectrolyte wetting agent in deionized water to form a wetting agent solution, and then adding the resulting wetting agent solution to the base slurry.
[0070] In some embodiments, the pre-dispersion rotation speed is 1200 rpm to 1400 rpm, for example, it can be 1200 rpm, 1220 rpm, 1250 rpm, 1280 rpm, 1300 rpm, 1320 rpm, 1350 rpm, 1380 rpm or 1400 rpm, and the time is 25 min to 35 min, for example, it can be 25 min, 26 min, 28 min, 30 min, 32 min, 34 min or 35 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0071] In some embodiments, the stirring speed is 10 rpm to 15 rpm, for example, 10 rpm, 11 rpm, 12 rpm, 13 rpm, 14 rpm or 15 rpm, and the time is 30 min to 45 min, for example, 30 min, 32 min, 35 min, 38 min, 40 min, 42 min or 45 min, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0072] In some embodiments, the homogenization pressure is 250 bar to 350 bar, for example, 250 bar, 260 bar, 270 bar, 280 bar, 290 bar, 300 bar, 310 bar, 320 bar, 330 bar, 340 bar or 350 bar, and the number of homogenization cycles is 1 to 3, for example, 1, 2 or 3 times.
[0073] This application further refines the agglomerated particles in the slurry through high-pressure homogenization, thereby improving the fineness and stability of the slurry and facilitating the acquisition of a more uniform and smooth coating film.
[0074] In some embodiments, the coating method includes any one of slot extrusion, doctor blade coating, or microgravure coating.
[0075] In some embodiments, the drying temperature is 100°C to 140°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0076] In some embodiments, the heat treatment temperature is 180°C to 250°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, or 250°C, and the time is 8h to 16h, for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, or 16h, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0077] The heat treatment step in this application is a key process for achieving bifunctional conversion. Within this temperature range, the benzene ring structure in the wetting agent molecules undergoes cross-linking and carbonization, and the polyethyleneimine segments also undergo pyrolytic carbonization, forming continuous carbon bridges between conductive particles. This significantly reduces contact resistance and improves the conductivity of the coating. If the temperature is too low, carbonization will be insufficient, and the conductivity enhancement effect will be limited; if the temperature is too high, the binder will easily degrade excessively, damaging the mechanical properties and adhesion of the coating.
[0078] One embodiment of this application also provides a battery electrode sheet, which contains at least the highly conductive carbon-coated current collector for reducing film surface defects as described in any of the above embodiments.
[0079] In some embodiments, the penetration resistance of the highly conductive carbon-coated current collector is ≤10 mΩ·cm. 2 For example, it could be 3mΩ·cm 2 3.5mΩ·cm 2 4mΩ·cm 2 4.5mΩ·cm 2 5mΩ·cm 2 5.5mΩ·cm 2 6mΩ·cm 2 6.5mΩ·cm 2 7mΩ·cm 2 7.5mΩ·cm 2 8mΩ·cm 2 8.5mΩ·cm 2 9mΩ·cm 2 9.5mΩ·cm 2 or 10mΩ·cm 2 However, this does not apply to all values listed; other unlisted values within the same range also apply.
[0080] In some embodiments, the number of defects on the film surface of the highly conductive carbon-coated current collector is ≤20 per m. 2 For example, it could be 1 / m 2 2 per m 2 4 units / m 2 6 units / m 2 8 per m 2 10 per m2 12 per m 2 14 per m 2 16 per m 2 18 per m 2 Or 20 per m 2 However, this does not apply to all values listed; other unlisted values within the same range also apply.
[0081] One embodiment of this application also provides a battery device, which includes at least the highly conductive carbon-coated current collector for reducing film defects as described in any of the above embodiments, or the battery electrode as described in any of the above embodiments.
[0082] The numerical range described in this application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0083] Preparation Example
[0084] This preparation example provides a method for synthesizing a polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer (PEI-PEG-SS), and the required raw materials are as follows:
[0085] ① Polyethyleneimine, purchased from Sinopharm Group, model number MW 70000, 50% aqueous solution (Wokai) 500g, Sinopharm code XW01900298609.
[0086] ② Polyethylene glycol monomethyl ether 400, purchased from Sinopharm Group, model number TCI-P2183 500g, Sinopharm code TP2183500G.
[0087] ③ Sodium styrene sulfonate was purchased from Sinopharm Group. The product name is 90% (Wokai) 500g, and the Sinopharm code is XW01269537606.
[0088] ④ Azobisisobutyronitrile (AIBN), the material can be purchased from Sinopharm Group, model AR (Shanghai Test), ≥99.0% 250g, Sinopharm code 80012461.
[0089] ⑤ Anhydrous potassium carbonate, purchased from Sinopharm Group, model AR (Shanghai Trial), ≥99.0% 250g, Sinopharm code 80012461.
[0090] ⑥ Dimethyl sulfoxide, purchased from Sinopharm Group, model number SigmaAldrich-D2650-100ML 100mL, Sinopharm code SD2650100ML.
[0091] ⑦ Anhydrous ethanol, material purchased from Sinopharm Group, model AR (Shanghai Trial), ≥99.7%, 5L / plastic drum, Sinopharm code 100092680.
[0092] ⑧ Azobisisobutyronitrile (AIBN), material purchased from Sinopharm Group, model AR (Shanghai Test), ≥99.0% 250g, Sinopharm code 80012461.
[0093] The specific synthesis method is as follows:
[0094] (a) Weigh 5g of polyethyleneimine and dissolve it in 50mL of anhydrous dimethyl sulfoxide. Add 4.1g of anhydrous potassium carbonate and transfer the solution to a three-necked flask equipped with a nitrogen protection device. Under nitrogen protection and a 70°C oil bath, slowly add a solution of 16.5g of polyethylene glycol monomethyl ether 400 in anhydrous dimethyl sulfoxide to the reaction system. After the addition is complete, continue the reaction at this temperature for 24h. This step involves the nucleophilic substitution of the Ts group in polyethylene glycol by the amino group of polyethyleneimine. After the reaction is complete, pour the reaction mixture into a large amount of ice-cold anhydrous diethyl ether to precipitate the product. Filter and collect the crude product. Repeat the dissolution-precipitation operation twice for purification. After vacuum drying, obtain the polyethyleneimine-polyethylene glycol intermediate.
[0095] (b) The above-mentioned polyethyleneimine-polyethylene glycol intermediate was dissolved in 30 mL of anhydrous dimethyl sulfoxide, and 5.8 g of sodium p-styrene sulfonate and 0.1 g of azobisisobutyronitrile were added. The reaction was carried out at 80 °C for 12 h. This step utilizes the remaining amino groups on polyethyleneimine to initiate a Michael addition reaction and azobisisobutyronitrile to initiate a slight free radical copolymerization, grafting sodium styrene sulfonate onto the polyethyleneimine backbone. After the reaction was completed, the reaction solution was placed in a dialysis bag and dialyzed in deionized water for 3 days to completely remove dimethyl sulfoxide and unreacted monomers. After freeze-drying, the final product, polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer, was obtained, which was a light yellow to brown solid, and was set aside for later use.
[0096] The raw materials required for subsequent embodiments and comparative examples are as follows:
[0097] ① Adhesive, polyacrylic acid-PAA.
[0098] ② Solvent: Deionized water.
[0099] ③ Conductive agent 1, carbon black, Cabot Chemical, model SHYT-150P.
[0100] ④ Conductive agent 2, graphite, purchased from Sinopharm Group, model: CP (Shanghai Test), ≥99.85% 100g, Sinopharm code 20019126.
[0101] ⑤ Wetting agent: the polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer obtained in the above preparation example.
[0102] ⑥ pH adjuster, sodium hydroxide, purchased from Sinopharm Group, model AR (Shanghai Trial) (tablets) 500g, Sinopharm code 10019764.
[0103] Example 1
[0104] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method, including the following steps:
[0105] (1) Preparation of basic slurry: Deionized water and polyacrylic acid solution (solid content 20wt%, viscosity 1500mPa·s) were mixed and diluted. The amount of polyacrylic acid solid added was 40wt% of the total solid mass of the slurry. Conductive agent (carbon black and graphite mass ratio 1:2, total addition amount was 60wt% of the total solid mass of the slurry) was added in two steps. In the first step, half of the conductive agent was added and dispersed at high speed at 2300rpm for 30min. In the second step, the remaining conductive agent was added and dispersed at high speed at 2300rpm for 60min. Deionized water was added to adjust the solid content of the slurry to 12wt% and dispersion was continued for 30min. 1mol / L sodium hydroxide solution was added to adjust the pH value of the slurry to 6.0 to obtain the basic slurry.
[0106] (2) Wetting agent mixing: The polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer powder obtained in the preparation example is mixed with deionized water to prepare a wetting agent solution with a solid content of 8wt%, and pre-dispersed at 1300rpm for 30min; the obtained wetting agent solution is added to the base slurry, and the amount of wetting agent solution added is 20% of the total mass of the slurry, and mixed evenly at a low speed of 12rpm for 40min.
[0107] (3) Coating and heat treatment: The mixed slurry was homogenized twice under a pressure of 300 bar, and then uniformly coated on the surface of aluminum foil using a slot extrusion coating method. The thickness of the single-sided carbon coating layer was controlled to be 1 μm and the coating width was 300 mm. After drying in an oven at 120℃, it was heat-treated at 200℃ for 12 h to obtain a highly conductive carbon-coated current collector.
[0108] Example 2
[0109] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the amount of wetting agent solution added is 15% of the total mass of the slurry. The remaining steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0110] Example 3
[0111] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the amount of wetting agent solution added is 10% of the total mass of the slurry. The remaining steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0112] Example 4
[0113] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the amount of wetting agent solution added is 5% of the total mass of the slurry. The remaining steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0114] Example 5
[0115] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that pH adjustment is not performed, and the natural pH of the slurry is about 4.2. The remaining steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0116] Example 6
[0117] This embodiment provides a highly conductive carbon-coated current collector that reduces film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the amount of polyacrylic acid solids added is 50 wt% of the total mass of the slurry solids, and the total amount of conductive agent added is adaptively adjusted to 50 wt% of the total mass of the slurry solids. The remaining steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0118] Example 7
[0119] This embodiment provides a highly conductive carbon-coated current collector with reduced film defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the heat treatment temperature is 180°C and the time is 16 hours. All other steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0120] Example 8
[0121] This embodiment provides a highly conductive carbon-coated current collector with reduced film surface defects and its preparation method. The only difference between this embodiment and Embodiment 1 is that the heat treatment temperature is 250°C and the time is 8 hours. All other steps and conditions are the same as in Embodiment 1, so they will not be described in detail here.
[0122] Comparative Example 1
[0123] This comparative example provides a carbon-coated current collector and its preparation method. The only difference between this example and Example 1 is that isopropanol is used as a wetting agent to replace the polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer. The amount added is the same. All other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0124] Comparative Example 2
[0125] This comparative example provides a carbon-coated current collector and its preparation method. The only difference between this example and Example 1 is that ungrafted benzenesulfonate polyethyleneimine-polyethylene glycol copolymer is used as the wetting agent. The remaining steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0126] Comparative Example 3
[0127] This comparative example provides a carbon-coated current collector and its preparation method. The only difference between this example and Example 1 is that no wetting agent is added. All other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0128] Comparative Example 4
[0129] This comparative example provides a carbon-coated current collector and its preparation method. The only difference between this example and Example 1 is that the 200°C heat treatment is not performed, and only the 120°C drying is performed. The remaining steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0130] Performance testing
[0131] (1) Surface tension test of slurry: A surface tension meter was used for testing using the platinum plate method. The slurry to be tested was placed in the sample cup to the specified height and allowed to stand until the temperature reached equilibration at 25°C. After the platinum plate was cleaned by burning with an alcohol lamp and completely wetted, it was vertically immersed about 2-3 mm below the surface of the slurry. The instrument automatically measured the maximum force value during the process of the slurry separating from the probe and converted it into a surface tension value. Each group of samples was measured three times, and the average value was taken. The probe was cleaned and dried before each measurement. At the same time, attention was paid to the stability of the slurry during the test to avoid sedimentation or volatilization affecting the accuracy of the data.
[0132] (2) Statistical analysis of film surface defects: Place the coated carbon current collector under a standard light source and visually count the number of visible defects such as white spots, gray spots, and shrinkage cavities per unit area. After multiple counts, take the average value.
[0133] (3) Transmission resistance test: Cut the carbon-coated current collector into 5cm×5cm samples and use a diaphragm resistance meter to test the transmission resistance and record the test data. Test 5 points for each sample and take the average value.
[0134] (4) Electrode resistance test: The positive electrode active material is coated on both sides of the carbon current collector, dried at 120°C, and the penetration resistance of the electrode is tested using a film resistance meter. After the test is completed, the experimental parameters are recorded.
[0135] The test results of the samples obtained in Examples 1-8 and Comparative Examples 1-4 are detailed in Table 1 below.
[0136] Table 1
[0137]
[0138] As shown in Table 1:
[0139] (1) The carbonized current collectors prepared in Examples 1 to 8 all exhibited low slurry surface tension and fewer film defects, while also having low penetration resistance, which fully demonstrates that the carbonizable polyelectrolyte wetting agent can simultaneously achieve excellent wetting effect and conductivity enhancement effect.
[0140] (2) As can be seen from Examples 1 to 4, as the amount of wetting agent added increases, the surface tension of the slurry gradually decreases, the number of defects on the film surface gradually decreases, and the penetration resistance also gradually decreases, which reflects the positive correlation between the amount of wetting agent and the dual-function effect.
[0141] (3) As can be seen from Example 1 and Comparative Example 1, although the traditional small molecule wetting agent isopropanol can reduce the surface tension and the number of defects on the film surface to a certain extent, its penetration resistance is much higher than that of Example 1, indicating that the small molecule wetting agent does not make a substantial contribution to the conductivity of the coating.
[0142] (4) As can be seen from Example 1 and Comparative Example 2, although the polyethyleneimine-polyethylene glycol copolymer without benzenesulfonate groups has good wetting effect, its penetration resistance is much higher than that of Example 1, indicating that the in-situ carbonization of benzenesulfonate groups is the key structural unit for achieving enhanced conductivity.
[0143] (5) As can be seen from Example 1 and Comparative Example 3, the surface tension of the slurry without the addition of wetting agent is as high as 49.46 mN / m, and the number of defects on the film surface is as high as 28 per m. 2 The poor conductivity further demonstrates the serious impact of insufficient wettability on film quality.
[0144] (6) As can be seen from Example 1 and Comparative Example 4, without high-temperature heat treatment, the wetting agent cannot undergo carbonization transformation, and the penetration resistance is much higher than that of Example 1, which further verifies the mechanism of heat treatment-induced in-situ carbonization to form conductive carbon bridges.
[0145] In summary, this application, through the combination of molecular design of carbonizable polyelectrolyte wetting agent and heat treatment process, successfully achieves a dual-effect technical effect with a single agent. Without increasing the amount of traditional conductive agent, it simultaneously improves the wettability of carbon coating slurry and the conductivity of the final coating, effectively solving the technical problem of difficulty in simultaneously addressing film defects and conductivity in existing carbon coating current collector technologies.
[0146] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. A highly conductive carbon-coated current collector for reducing film surface defects, comprising a current collector substrate and a conductive coating formed on at least one surface of the current collector substrate, characterized in that, The raw materials for preparing the conductive coating include at least a carbonizable polyelectrolyte wetting agent; The carbonizable polyelectrolyte wetting agent is a polyethyleneimine-polyethylene glycol-benzenesulfonate graft copolymer.
2. The high conductivity carbon-coated current collector for reducing film surface defects according to claim 1, characterized in that, The carbonizable polyelectrolyte wetting agent is added to the slurry in the form of an aqueous solution, and the solid content of the aqueous solution is 5wt%~10wt%, and the amount of the aqueous solution added is 5%~20% of the total mass of the slurry.
3. The high conductivity carbon-coated current collector for reducing film surface defects according to claim 1 or 2, characterized in that, The raw materials for preparing the conductive coating also include conductive agents, binders, and pH adjusters; The conductive agent includes carbon black and / or graphite; And / or, based on the dry weight of the conductive coating, the amount of the conductive agent added is 50wt%~60wt%; And / or, the adhesive comprises at least one of polyacrylic acid, waterborne acrylate copolymer, carboxymethyl cellulose or styrene-butadiene rubber, with a viscosity of 800 mPa·s to 3500 mPa·s; And / or, based on the dry weight of the conductive coating, the amount of adhesive added is 40wt%~50wt%; And / or, the pH adjuster includes sodium hydroxide and / or sodium carbonate.
4. The high conductivity carbon-coated current collector for reducing film surface defects according to claim 1 or 2, characterized in that, The current collector substrate includes any one of aluminum foil, copper foil, nickel foil, or titanium foil; And / or, the thickness of the conductive coating on one side is 0.5μm to 3μm.
5. A method for preparing a highly conductive carbon-coated current collector as described in any one of claims 1 to 4, characterized in that, The preparation method includes at least the following steps: adding a carbonizable polyelectrolyte wetting agent to a base slurry, stirring and homogenizing the slurry, coating the resulting slurry onto at least one side of the current collector substrate, and drying and heat-treating the slurry to obtain the highly conductive carbon-coated current collector.
6. The method for preparing the highly conductive carbon-coated current collector according to claim 5, characterized in that, The preparation method of the base slurry includes: first mixing the binder and deionized water, then adding the conductive agent step by step, adjusting the pH value to obtain the base slurry; The conductive agent is added in two steps, and after each step, it is dispersed at a speed of 2000 rpm to 2600 rpm. The dispersion time for the first step is 25 min to 35 min, and the dispersion time for the second step is 55 min to 65 min. And / or, the target pH value of the base slurry is 5 to 7.
7. The method for preparing the highly conductive carbon-coated current collector according to claim 5, characterized in that, The carbonizable polyelectrolyte wetting agent is added in the form of an aqueous solution, comprising: first pre-dispersing the carbonizable polyelectrolyte wetting agent in deionized water to form a wetting agent solution, and then adding the obtained wetting agent solution to the base slurry; The pre-dispersion rotation speed is 1200 rpm to 1400 rpm, and the time is 25 min to 35 min.
8. The method for preparing the highly conductive carbon-coated current collector according to claim 5, characterized in that, The stirring speed is 10 rpm to 15 rpm, and the stirring time is 30 min to 45 min; And / or, the homogenization process is carried out at a pressure of 250 bar to 350 bar, and the number of homogenization cycles is 1 to 3. And / or, the drying temperature is 100℃~140℃; And / or, the heat treatment temperature is 180℃~250℃, and the time is 8h~16h.
9. A battery electrode, characterized in that, The battery electrode contains at least one highly conductive carbon-coated current collector that reduces film surface defects as described in any one of claims 1 to 4; The penetration resistance of the highly conductive carbon-coated current collector is ≤10 mΩ·cm. 2 ; And / or, the number of defects on the film surface of the highly conductive carbon-coated current collector is ≤20 per m. 2 .
10. A battery device, characterized in that, The battery device includes at least the highly conductive carbon-coated current collector for reducing film defects as described in any one of claims 1 to 4, or the battery electrode as described in claim 9.
